Ensuring Job Satisfaction for Managing People at Work - Molla , Md. Istiaque Hossain (Global Disclosure of Economics and Business, 2015)
Job satisfaction is the most common word in an organization that represents one of the most complex areas facing today’s managers when it comes to managing their employees. Job satisfaction is a psychological state of man when an individual’s needs and aspirations fulfilled in a workplace, people are contented and happy with one’s job. Satisfactory pay, autonomy challenging work, participation in decision making, supportive working conditions, supportive colleagues and participatory management all these are the common factors of job satisfaction. Studies have demonstrated an unusually high impact on the job satisfaction for the motivation of workers, while the level of motivation has an impact on productivity, and hence also on the performance of organizations. Unfortunately, in our region, job satisfaction has not still received the proper attention from neither scholars nor managers of various business organizations. Due to individual differences job satisfaction has become a diverse issue. All the facets of job satisfaction have to be understood and considered for sustaining people. Conflict with peers and superiors, being deprived of fair pay and career development opportunities, lack of recognition, alienation are the vital causes of job dissatisfaction which adversely affects the quality of work and ultimately leads to organizational instability. Positive feedback, recognition, fair pay and other benefits, rewards, participation in decision making, congenial working conditions provide job satisfaction that contributes sustaining and retaining people in an organization. In fact there is no final definition of what career represents.